The rehabilitation of a competitive swimmer with an asymmetrical breaststroke movement pattern - Carson, P. A. (Manual therapy, 1999)
This case study describes the treatment and management of an 11-year-old competitive swimmer who was repeatedly disqualified from races because of an asymmetrical movement pattern, otherwise called stroke. The treatment was based on the impairments found during the physical examination that were considered relevant to the physical dysfunction resulting in the asymmetrical stroke. This gave rise to the hypothesis that muscle imbalances around the right shoulder and left hip, together with a relative restriction of motion in these joints, were resulting in the transmission of forces up and down the kinetic chain and that these were contributing factors to the asymmetrical breaststroke stroke. An eclectic approach was used in the analysis, and the subsequent treatment and management, of the problem. To achieve the goal of a symmetrical stroke, the muscle balance/imbalance approaches of Janda (1994), Sahrmann (1988) and Kendall et al. (1993) were used. The joint impairments were treated with techniques described by Maitland (1986) and Mulligan (1996), while the exercise programme included the core/stabilizing approach presented by Blanch (1997). The treatment period consisted of four phases of 3 weeks each. The result indicates that early identification and treatment of muscle imbalance syndromes and relative joint restrictions by the physiotherapist and coach working together may be useful in establishing good movement patterns and technique for competitive swimmers.